2017
DOI: 10.1021/acs.jpclett.7b01829
|View full text |Cite
|
Sign up to set email alerts
|

Diagrammatic Exciton Basis Theory of the Photophysics of Pentacene Dimers

Abstract: Covalently linked acene dimers are of interest as candidates for intramolecular singlet fission. We report many-electron calculations of the energies and wavefunctions of the optical singlets, the lowest triplet exciton and the triplet-triplet biexciton, as well as the final states of excited state absorptions from these states in a family of phenyl-linked pentacene dimers. While it is difficult to distinguish between the triplet and the triplet-triplet from their transient absorptions in the 500-600 nm region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
89
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(103 citation statements)
references
References 57 publications
(238 reference statements)
13
89
1
Order By: Relevance
“…A similar result was found in theoretical work by Mazumdar and coworkers who assigned a photoinduced transition near 1400 nm in pentacene dimers to from 1 (T 1 T 1 ) / S 2 . 61,62 Such transitions between one and two exciton manifolds have been reported previously in work by the Knoester group. 63 Additional information can be gleamed from TAS by probing even further into the infrared; Grieco et al have identified transitions between 1 (T 1 T 1 ) and S 1 that lie near 0.3 eV.…”
Section: (T 1 T 1 ) Revealed By a Variety Of Spectroscopic Techniquessupporting
confidence: 78%
See 1 more Smart Citation
“…A similar result was found in theoretical work by Mazumdar and coworkers who assigned a photoinduced transition near 1400 nm in pentacene dimers to from 1 (T 1 T 1 ) / S 2 . 61,62 Such transitions between one and two exciton manifolds have been reported previously in work by the Knoester group. 63 Additional information can be gleamed from TAS by probing even further into the infrared; Grieco et al have identified transitions between 1 (T 1 T 1 ) and S 1 that lie near 0.3 eV.…”
Section: (T 1 T 1 ) Revealed By a Variety Of Spectroscopic Techniquessupporting
confidence: 78%
“…An innovative approach to reduce overlapped signals was reported in two independent studies on crystals of rubrene, 65 and hexacene. 57 In both cases, highly polarized singlet absorption was used to provide a reduction in signal overlap and provided a key 15,55,61 insight: the coherent pathway for m (T 1 T 1 ) promotion. The presence of a nearly instantaneous signal at time zero is most clearly observed because of the suppression of singlet signals based on the selective probing along a specific facet.…”
Section: (T 1 T 1 ) Revealed By a Variety Of Spectroscopic Techniquesmentioning
confidence: 99%
“…(iii) Finally, to what extent does the 1 (TT) 1 ESA resemble ESA from the free triplet T 1 as the number of phenyl linkers is increased? Experiments indicate decreasing coupling [13,35] between the two triplets with increasing n. Our previous calculations for BPn could not be performed for n > 1 because of the large size of the TIPS-pentacene monomer [17].…”
Section: Transient Absorptionsmentioning
confidence: 96%
“…Absorptions from FE excitations shown in Fig. 2(a) are polarized along the short axes of the monomers [17,29] while CT excitations are predominantly polarized along the long molecular axis of the dimer.…”
Section: Ground State Absorptionmentioning
confidence: 99%
“…Contiguous dimers have shown that the singlet and triplet pair energy manifolds are mixed, with allowed TT-S n optical transitions. 32,62 Furthermore, radiationless decay of triplet pairs has been shown to slow down as chromophore proximity decreases. From this, we suggest that the triplet pair decays through coupling to singlet vibronic modes, permitting a rapid and spin-allowed route back to the ground state.…”
Section: Introductionmentioning
confidence: 99%